SEASONAL INFLUENCE ON COLONY PERFORMANCE INDEX (CPI) IN APIS CERENA INDICA UNDER BANGALORE CONDITION - PRADEEPA, S.D.; BHAT, N.S.; PRABHAVATHI, M.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Five colonies of 4 frame strength A. cerana indica were studied for the colony performance index for a period of one month during different season's viz. rainy, winter and spring seasons. The peak foraging activity was assessed from 08:00 h to 12:00 h in respective seasons before recording CPI in the experimental colonies. The peak foraging activity was at 9:30 to 10:30 h, 10:00 to 11:00 h and 8:30 to 9:30 hours in rainy, winter and spring seasons respectively. The mean Colony Performance Index was 5.46 in rainy, 14.14 in winter and 7.28 in spring and these showed significant differences among themselves. There was significant increase in CPI for successive three weeks from the start of the experiment, irrespective of seasons.